Role of porosity on the equilibration kinetics in electrical conductivity relaxation experiments. (9th July 2021) - Banner, Jane; Ghosh, Emily; Gopalan, Srikanth
Abstract: The role of porosity on the equilibration kinetics in electrical conductivity relaxation (ECR) experiments is highlighted. Both porous and dense conductivity bars are used to determine the chemical oxygen surface exchange coefficient ( k chem ) of neodymium nickelate Nd2 NiO4+δ (NNO) from 600 to 800 °C. Using porous bars allows for quicker ECR experiments during which the conductivity transient is rate limited only by oxygen surface exchange which enables the use of a simple transient model. Additionally, porous bars have similar microstructures to porous electrodes which means they are critical for determining the oxygen exchange kinetics of realistic electrodes. ECR results on dense bars with porous coatings are also presented. The conductivity transients of dense and porous bars both show similar trends with oxygen partial pressure. Additionally, both porous and dense bars show a difference between oxidation and reduction transients with oxidation transients being faster than reduction transients. Graphical abstract: Image 1 Highlights: Porous materials offer unique advantages to study redox surface exchange kinetics. Reduced diffusion distances eliminate the dependence of kinetics on diffusion. Approach to thermodynamic equilibrium is faster in porous materials. Oxidation kinetics of neodymium nickelate are faster than the reduction kinetics. Surface exchange kinetics in neodymium nickelate show no temperature dependence.